Diagnóstico para implantação de um sistema de gestão ambiental em uma instituição federal de ensino - Mendonça, Bruna Arduini (Universidade Federal de São Carlos, 2015)
The Brazilian government has implemented policies and procedures that govern the actions of the society and entities own state in order to promote greater environmental awareness and actions that mitigate negative environmental impacts, such as the Environmental Agenda program in Public Administration (A3P). The adoption of an Environmental Management System (EMS) formalized by an educational institution can contribute to the awareness and the spread of the importance of environmental issues. The Campus Uberaba of Federal Institute of Education, Science and Technology of Triângulo Mineiro (IFTM - Campus Uberaba) is an educational institution that seeks to establish an environmental management system. This study aimed to carry out an environmental diagnosis in IFTM - Campus Uberaba as a way to aid in the definition of social and environmental responsibility policies and the implementation of an EMS in the institution. Exploratory study was conducted in order to identify existing environmental standards to which the IFTM - Campus Uberaba is subject, as well as meet other voluntary environmental management practices by public institutions and / or higher education that could serve as a model for the institution. From the management reporting analysis, environmental control report, bidding notices, pedagogical projects of the courses offered by the institution, and also through direct observation, the main environmental aspects and impacts from campus´s processes and services have been identified, and existing environmental practices. It was verified that, over time, there was an intensification of government actions to mobilize their public institutions in the adoption of sustainability and environmental responsibility criteria. In IFTM - Campus Uberaba, environmental impacts information were identified on the physical, biotic and socioeconomic means and the action already present of a solid waste management project and a joint selective collection program. It was observed that the bidding notices practiced on campus do not include sustainability criteria in the procurement of materials and services and, for the discard practices of the institution, the legislation that deals with it has been obeyed. It was also observed that it is prevalent the use of virgin paper and disposable cups in the institution. As for the teaching practice it was found that the environmental issues, social and environmental responsibility and sustainable development are covered by most courses. The analysis of the survey of voluntary environmental management practices of some higher education institutions and other public institutions has observed that for the IFTM - Campus Uberaba assume its social and environmental responsibility are necessary several actions of its senior management to motivation and conviction of their community. From these findings it was concluded that the IFTM - Campus Uberaba may adopt changes and fixes in existing shares to fit the criteria and environmental requirements in voluntary standards, either by ISO 14001 or as the A3P, which should promote a management participatory, enhancing existing initiatives and involving the whole community.
Keywords: Instituição pública de ensino superior; Sistema de gestão ambiental; A3P; Public institution of higher education; Environmental management system; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS